2014
DOI: 10.4038/sljer.v2i1.101
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the evolution of modern financial science

Abstract: Financial science or financial economics, as a sub-discipline in economics, has recorded a remarkable progress during the past fifty years. Finance deals with allocation of various assets and liabilities in the long run within uncertain conditions. Hence, the study of finance involves inquiring, explaining and predicting a diverse and growing number of financial instruments, institutions, and markets, as well as the relationship of their behavior to other economic variables. The study of finance has, therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, there are reports that the sale of seasonal fruits ripened with harmful chemicals and pesticides continues in the rural markets, and the authorities concerned are yet to launch any steps to deal with these irresponsible business practices (Reporter, 2009). Similarly, in Sri Lanka, it is also found that the quality of products traded by SIEs is low and regulation of the business environment is weak (Dayaratna‐Banda, 2007).…”
Section: Exploring Customer Awareness Socially‐responsible Business Practices Of Sies and Customer Loyalty At The Bop Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are reports that the sale of seasonal fruits ripened with harmful chemicals and pesticides continues in the rural markets, and the authorities concerned are yet to launch any steps to deal with these irresponsible business practices (Reporter, 2009). Similarly, in Sri Lanka, it is also found that the quality of products traded by SIEs is low and regulation of the business environment is weak (Dayaratna‐Banda, 2007).…”
Section: Exploring Customer Awareness Socially‐responsible Business Practices Of Sies and Customer Loyalty At The Bop Levelmentioning
confidence: 99%
“…The bottom two segments are relatively neglected in the mainstream BoP discourse. This is despite growing evidences of irresponsible business practices being adopted by SIEs and SMEs, in the South Asian region ignoring customer rights and taking advantage of the vulnerability of the BoP customers (Reporter, 2009; Dayaratna‐Banda, 2007; Rashmi, 2003). The study aims to fill the void in the literature by focusing on the under‐researched segments at the lower end of the BoP to gain insights into the level of awareness of their rights, their expectation from businesses and customer loyalty.…”
Section: Introductionmentioning
confidence: 99%